Family Quality of Life in Children with Severe or Profound Disability: Home Versus Residential Care. Issue 1 (January 2023) - Karni-Visel, Yael; Nasser, Kareem; Manishevitch, Hofit; Akrt, Sahar; Schertz, Mitchell
ABSTRACT: Background: Most children with severe and profound intellectual disability (SPID) are cared for in their homes, according to current recommendations. Yet, their families face marked emotional, health, and economic challenges. Aims: The aim of this study was to examine family quality of life (FQOL) along with psychological and health factors among families who raise children with SPID at home versus those residing in residential care. Methods: Sixty caregivers of children aged 2 to 18 years ( M = 8.81, SD = 4.62) with SPID (developmental quotient/intellectual quotient <35), living at home (38 caregivers—"home group") or in residential care (22 caregivers—"residential group"), completed the FQOL Survey, Beck Depression Inventory, Parental Stress Index, Shame and Guilt Scale, and Health and Demographic questionnaires. Results: FQOL for most domains and dimensions was rated better among families whose child resides in residential care compared with families who raise their child at home. Similarly, parental stress relating to the child was worse among families who raise their children at home. No significant differences between the 2 groups were noted on other psychological or health measures. Conclusion: Family and individual needs for those raising a child with SPID at home should be addressed when planning policy and interventions.